HAERI ISFAHANI AND NEW THOUGHTS IN PRINCIPLE SCIENCE - Nejad, Malih Foroutan; Khoshkar, Mohamad Bahrami (International Journal of Psychosocial Rehabilitation, 2020)
Researching and studying the lives of educators and elders in science and literature and getting to know their opinions and beliefs is a fun and moving work. In introducing elders, especially religious scholars, it is customary to first introduce a person in terms of family history, date of birth and death, schooling, and professors, students, and academic works left behind by him, and usually enough. While it is worthwhile to examine the writings of these elders carefully and to get their views recognized and introduced. Among the jurists are those who have been the source of dramatic effects in expressing new ideas and ideas. Mohammad Hussein Haeri is one of these jurisprudents, and his book Fosoul Al- Gharavieh is a turning point in the history of basic science. Allama Sheikh Mohammad Hussein ibn Abdul Rahim Haeri Isfahani did not imitate his predecessors in his inference of jurisprudence. His meticulousness, scientific courage, and freedom of thought in the innovation and expression of famous anti-fatwas are among the highlights of his scientific life.